Adopsi Internet of Things dalam Budidaya Labu Madu di Kawasan Pertanian Urban - Cucuk Wawan Budiyanto; Della Astri Widayani; Iqlima Alna; Az-Zahra Jasmine Heru Putri; Baruna Ghazy Putra Patria Negara; Muhammad Ilham Rizki Putra; Fathin Althafia Wiyono; Alfira Andra Hestian; Meliyana Kusumawati; Febriana Yuliani; Diah Rachmawati Octaviani (DEDIKASI: Community Service Reports, 2024)
Badran Village is known for its signature honey pumpkin cultivation, which is managed by the village's Women Farmers Group (KWT). These honey gourds have a high selling value in the fruit market, ranging from Rp35,000 to Rp80,000 per kilogram. However, the crop watering system in Badran Village is still conventional, causing challenges in maintaining sufficient and regular irrigation for the honey pumpkin crop which is highly dependent on water supply. In an effort to increase productivity and water-use efficiency in honey pumpkin cultivation, the KKN Team of Sebelas Maret University Group 33 proposed a work program in the form of an Automatic Drip Irrigation System. This system utilizes Internet of Things (IoT) technology with NodeMcu ESP8266 as the control board and Blynk platform to allow remote supervision and control of the device via smartphone. The use of this technology is expected to help KWT and other urban farmers in maximizing their agricultural yields and reducing water wastage. The results of the KKN Group 33 activities in Badran Village show that the construction of the drip irrigation system went smoothly according to schedule. The construction of this automatic drip irrigation system is expected to help KWT in increasing the potential of honey pumpkin farming as well as agricultural tourism attraction in their village. This research also provides room for improvement by incorporating soil moisture sensors or automatic scheduling based on time, which can further increase the efficiency of this system